HJT battery back metallization paste composition, HJT battery back metallization paste and HJT battery
By developing a high conductivity metallization slurry composition suitable for the back of the HJT battery, the problems of high cost of metallization slurry and low photoelectric conversion efficiency on the back of the HJT battery are solved, and the effects of increasing short-circuit current and reducing metallization cost are achieved.
Patent Information
- Application Number
- CN202310686162.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-09
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-06-09
AI Technical Summary
The metallization slurry on the back of the HJT battery has high cost and low photoelectric conversion efficiency.
A metallized slurry composition on the back of the HJT battery was developed, including 90 to 95 parts of metal powder, 0.5 to 10 parts of organic carrier and 0.5 to 5 parts of solvent. The metal powder consists of silver powder and silver-covered copper powder. The D90 particle size of silver powder is 4 to 11 μm and the D90 particle size of silver coated copper powder is 5 to 8 μm. The mass ratio and particle size ratio of silver powder and silver-covered copper powder are optimized to improve conductivity and printability.
The viscosity and amount of metallization slurry on the back of the HJT battery are reduced, and the line width of the secondary grid lines on the back are increased, thereby increasing the short-circuit current, taking into account the photoelectric conversion efficiency and low metallization cost of the HJT battery.
Smart Images

Figure CN116682593B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of HJT batteries, and in particular to a HJT battery back metallization paste composition, an HJT battery back metallization paste and an HJT battery. Background Art
[0002] Heterojunction technology (HJT) combines the dual advantages of crystalline silicon solar cells and thin film technology. From a structural point of view, HJT cells deposit intrinsic amorphous silicon thin films (ia-Si:H) and p-type amorphous silicon thin films (pa-Si:H) on the front of the silicon wafer, and then deposit transparent oxide conductive thin films TCO. On the back of the silicon wafer, intrinsic amorphous silicon thin films (ia-Si:H) and n-type amorphous silicon thin films (na-Si:H) are deposited in sequence to form a back surface field, and then transparent oxide conductive thin films TCO are deposited, and finally metallization is completed. HJT cells have attracted much attention in the industry due to their low cost, low temperature coefficient, no light decay, high stability, and low process temperature. They are an important technical direction for the future development of high-efficiency and low-cost photovoltaics.
[0003] The main problem restricting the mass production of HJT batteries is the high cost of metallization. Due to battery performance requirements such as TCO film, only low-temperature curing silver paste can be used to make electrode sub-grid lines. In order to achieve high conductivity, the solid content of low-temperature curing silver paste is relatively high, generally around 92-95%, so the paste cost per unit weight is relatively high. At the same time, the sub-grid lines need to be printed on both the front and back of the battery, so the paste consumption of each battery is relatively large. In order to further promote the market application of HJT batteries, it is particularly important to reduce the cost of low-temperature curing paste.
[0004] Silver-coated copper technology forms silver coatings of varying thicknesses on the surface of ultrafine copper powder by chemical plating, and adjusts the silver-copper ratio of the slurry to improve the antioxidant capacity of the silver-coated copper powder, thereby achieving the cost reduction goal of replacing part of the silver with copper. At the same time, since copper is easily oxidized at high temperatures, resulting in a doubling of resistivity, silver-coated copper powder is very suitable for the development of low-temperature curing slurries for HJT batteries.
[0005] At present, HJT cells on the market use the same low-temperature curing silver-copper paste on both the front and back sides. But in fact, when HJT cells are working, the front and back sides play different roles, such as Figure 1As shown. In order to maximize efficiency, the line width of the front auxiliary grid line should be small to increase the light receiving area of the battery. The line width of the back auxiliary grid line should be large to improve light reflectivity, increase the number of photons generated in the battery, and increase current. On the other hand, the mainstream HJT metallization production line on the market uses a back screen with a larger opening than the front screen. This makes the printing of the back slurry less difficult. Therefore, in order to improve the photoelectric conversion efficiency of HJT and reduce the cost of metallization, it is very necessary to develop a low-temperature curing silver-copper paste specifically for the back of HJT batteries. Summary of the invention
[0006] The main purpose of the present invention is to provide a HJT battery back metallization paste composition, an HJT battery back metallization paste and an HJT battery, so as to solve the problems of high cost of HJT battery back metallization paste and low photoelectric conversion efficiency of HJT battery in the prior art.
[0007] In order to achieve the above-mentioned object, according to one aspect of the present invention, a HJT battery back side metallization paste composition is provided, which comprises, by weight, 90 to 95 parts of metal powder, 0.5 to 10 parts of organic carrier and 0.5 to 5 parts of solvent; wherein the metal powder comprises silver powder and silver-coated copper powder, the silver powder comprises a first silver powder and a second silver powder, the D90 particle size of the first silver powder is ≥ the D90 particle size of the second silver powder, and the D90 particle size of the first silver powder is 4 to 11 μm.
[0008] Furthermore, the mass ratio of the silver powder to the silver-coated copper powder is 0.5-2:1, preferably the mass ratio of silver to copper in the silver-coated copper powder is 0.05-0.3:1, and preferably the D90 particle size of the silver-coated copper powder is 5-8 μm.
[0009] Further, the first silver powder is flaky silver powder, and the second silver powder is spherical silver powder. The mass ratio of flaky silver powder to spherical silver powder is preferably 23:1-8; the flake thickness of the flaky silver powder is preferably 0.05-0.1 μm, and the D90 particle size of the spherical silver powder is preferably 300-800 nm; further, the mass ratio of flaky silver powder, spherical silver powder and silver-coated copper powder is preferably 46:16:31; or, the first silver powder and the second silver powder are both flaky silver powder; the D90 particle size of the flaky silver powder is 4-11 μm, and the flake thickness of the flaky silver powder is preferably 0.05-0.1 μm. Further, the mass ratio of flaky silver powder to silver-coated copper powder is preferably 62:31.
[0010] Furthermore, the organic carrier is selected from any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, hexahydrophthalic acid bisglycidyl ester, and tetrahydrophthalic acid bisglycidyl ester.
[0011] Furthermore, the solvent is selected from any one or more of dibutyl carbonate, N,N-dimethyldecylamine, diethylene glycol-2-ethylhexyl ether, diethylene glycol monohexyl ether, diethylene glycol butyl ether acetate, diethylene glycol butyl ether, dodecanol ester, pineneol, and methyl adipate.
[0012] Furthermore, the above-mentioned HJT battery back metallization paste composition also includes 0.5 to 1.5 parts of an auxiliary agent, and the auxiliary agent is preferably selected from any one or more of a thixotropic agent, a silane coupling agent, and a dispersant.
[0013] According to another aspect of the present invention, a HJT battery back metallization paste is provided. The HJT battery back metallization paste is prepared by mixing the above-mentioned HJT battery back metallization paste composition.
[0014] Furthermore, the viscosity of the above-mentioned HJT battery back metallization paste is 50 to 800 Pa.s, and preferably the viscosity of the HJT battery back metallization paste at 10 revolutions is 200 to 550 Pa.s.
[0015] According to another aspect of the present invention, there is provided an HJT battery, comprising a front metallization layer, an oxide conductive film TCO, a p-type amorphous silicon film pa-Si:H, an intrinsic amorphous silicon film ia-Si:H, a silicon wafer, an intrinsic amorphous silicon film ia-Si:H, an n-type amorphous silicon film na-Si:H, an oxide conductive film TCO, and a back metallization layer stacked in sequence, wherein the back metallization layer is formed by curing the above-mentioned HJT battery back metallization slurry.
[0016] Furthermore, the interval between adjacent auxiliary gate lines of the back metallization layer is 0.5-2.5 mm, preferably the width of each auxiliary gate line is 35-75 μm, and preferably the aspect ratio of each auxiliary gate line is 2-4:10.
[0017] Applying the technical solution of this application, this application targets the characteristics of the back metallization of HJT batteries. By selecting silver powder with a particle size of D90 in the above range, on the one hand, it is beneficial to optimize the dense packing structure of the metal powder and develop a high-conductivity slurry that is particularly suitable for screen printing on the back of large-opening HJT batteries. On the other hand, it is beneficial to improve the compatibility of organic carriers and metal powders, improve the printability of the metallization slurry on the back of HJT batteries, and at the same time, reduce the viscosity and dosage of the metallization slurry on the back of HJT batteries, increase the line width of the back sub-grid lines, and thus increase the short-circuit current. The combination of silver powder and silver-coated copper powder helps to improve the conductivity of the metallization slurry on the back of HJT batteries, thereby helping to balance the photoelectric conversion efficiency and low metallization of HJT batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0019] Figure 1 SEM images of different metal powders provided according to Example 1 of the present invention are shown;
[0020] Figure 2 An optical photograph showing the dispersion of silver-coated copper powder tested by the vial sedimentation method according to the present invention; and
[0021] Figure 3 The graphs showing the viscosity variation of different slurries at different rotation speeds provided in Examples 1 to 4 of the present invention are shown. DETAILED DESCRIPTION
[0022] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0023] As analyzed in the background technology of this application, the HJT battery back metallization paste in the prior art has the problems of high cost and low photoelectric conversion efficiency of the HJT battery. In order to solve this problem, this application provides a HJT battery back metallization paste composition, HJT battery back metallization paste and HJT battery.
[0024] In a typical embodiment of the present application, a HJT battery back side metallization paste composition is provided, which comprises, by weight, 90 to 95 parts of metal powder, 0.5 to 10 parts of organic carrier and 0.5 to 5 parts of solvent; wherein the metal powder comprises silver powder and silver-coated copper powder, the silver powder comprises a first silver powder and a second silver powder, the D90 particle size of the first silver powder is ≥ the D90 particle size of the second silver powder, and the D90 particle size of the first silver powder is 4 to 11 μm.
[0025] This application aims at the characteristics of the back metallization of HJT batteries. By selecting silver powder with a D90 particle size in the above range, on the one hand, it is beneficial to optimize the dense packing structure of the metal powder and develop a high-conductivity slurry that is particularly suitable for screen printing on the back of large-opening HJT batteries. On the other hand, it is beneficial to improve the compatibility of organic carriers and metal powders, improve the printability of the metallization slurry on the back of HJT batteries, and at the same time, reduce the viscosity and dosage of the metallization slurry on the back of HJT batteries, increase the line width of the back sub-grid lines, and thus increase the short-circuit current. The combination of silver powder and silver-coated copper powder helps to improve the conductivity of the metallization slurry on the back of HJT batteries, thereby helping to balance the photoelectric conversion efficiency and low metallization cost of HJT batteries.
[0026] In one embodiment of the present application, the mass ratio of the above-mentioned silver powder to the silver-coated copper powder is 0.5-2:1, preferably the mass ratio of silver to copper in the silver-coated copper powder is 0.05-0.3:1, and preferably the D90 particle size of the silver-coated copper powder is 5-8 μm.
[0027] The preferred mass ratio of the silver powder to the silver-coated copper powder helps to improve the synergistic effect of the two, thereby achieving both low cost and appropriate resistivity.
[0028] In one embodiment of the present application, the first silver powder is flaky silver powder, and the second silver powder is spherical silver powder. The mass ratio of flaky silver powder to spherical silver powder is preferably 23:1-8; the flake thickness of the flaky silver powder is preferably 0.05-0.1 μm, and the D90 particle size of the spherical silver powder is preferably 300-800 nm; further, the mass ratio of flaky silver powder, spherical silver powder and silver-coated copper powder is preferably 46:16:31; or, the first silver powder and the second silver powder are both flaky silver powder; the D90 particle size of the flaky silver powder is 4-11 μm, and the flake thickness of the flaky silver powder is preferably 0.05-0.1 μm. Further, the mass ratio of flaky silver powder to silver-coated copper powder is preferably 62:31.
[0029] The present invention preferably compounds the above large-particle size flaky silver powder and small-particle size spherical silver powder, and further preferably sets the mass ratio of the two within the above range, which is beneficial to optimizing the dense packing structure and density of the metal powder, improving the conductivity of the slurry, and thus solving the problem of high resistivity of the silver-coated copper powder, and further improving the conductivity and photoelectric conversion efficiency of the back of the HJT battery.
[0030] In one embodiment of the present application, the organic carrier is selected from any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, hexahydrophthalic acid diglycidyl ester, and tetrahydrophthalic acid diglycidyl ester.
[0031] Preferably, the above organic carriers shrink upon curing to form more conductive paths and can be better adapted to the above metal powders, thereby improving the overall uniformity of the metallization slurry on the back of the HJT battery and the conductivity after metallization.
[0032] In one embodiment of the present application, the above-mentioned solvent is selected from any one or more of dibutyl carbonate, N,N-dimethyldecylamine, diethylene glycol-2-ethylhexyl ether, diethylene glycol monohexyl ether, diethylene glycol butyl ether acetate, diethylene glycol butyl ether, dodecanol ester, pineneol, and methyl adipate.
[0033] The dispersibility of silver-coated copper powder and silver powder in solvents is different, and more than 90% of the components in the metallization slurry on the back of the HJT battery are metal powders. Therefore, the dispersibility of the metal powders is directly related to the physical properties of the slurry and the efficiency performance after curing. The preferred solvents above are beneficial to taking into account the dispersibility of both silver-coated copper powder and silver powder therein.
[0034] Preferably, the solvent screening method of the present application is the vial sedimentation method: use a transparent glass sample bottle with a volume of 10 mL, weigh 2 g of composite metal powder and place it in the sample bottle. The composite metal powder includes silver powder and silver-coated copper powder, and the silver powder includes a first silver powder and a second silver powder. Use a dropper to drop 5 g of different solvents into the sample bottles containing the composite metal powder. Shake thoroughly to evenly disperse the powder, and take a photo and record it as T0. Place the sample bottle flat on the laboratory bench, let it stand for 30 minutes at room temperature, and then take a photo, which is recorded as T30. Compare the sedimentation rates of the composite metal powder in different solvents to determine the dispersibility of the composite metal powder in different solvents. A fast sedimentation rate proves poor dispersibility, and vice versa. Figure 2 As shown: According to the sedimentation rate of the composite metal powder in different solvents at T30, it can be judged that the dispersibility of the composite metal powder in different solvents is ranked from good to bad as dibutyl carbonate>N,N-dimethyldecylamine>diethylene glycol-2-ethylhexyl ether>diethylene glycol monohexyl ether>tripropylene glycol methyl ether, wherein A represents dibutyl carbonate, B represents diethylene glycol-2-ethylhexyl ether, C represents tripropylene glycol methyl ether, D represents N,N-dimethyldecylamine, and E represents diethylene glycol monohexyl ether. This method has the advantages of low cost, short time consumption, intuitive test results and high result reproducibility, and provides an effective means to improve the compatibility of solvents and composite metal powders. The diethylene glycol butyl ether acetate, diethylene glycol butyl ether, dodecyl alcohol ester, pinene alcohol or methyl adipate solvents further selected by the above similar method also have good dispersibility for the above composite metal powders.
[0035] In order to further improve the adjustability of the performance of the HJT battery back metallization paste, so as to adjust its performance in a timely manner, the HJT battery back metallization paste composition preferably also includes 0.5 to 1.5 parts of an auxiliary agent, and the auxiliary agent is preferably selected from any one or more of a thixotropic agent, a silane coupling agent, and a dispersant, so as to help assist in adjusting the viscosity and other properties of the HJT battery back metallization paste. Among them, the thixotropic agent is preferably selected from any one or more of an amide lubricating thixotropic agent, a hydrogenated castor oil thixotropic agent, and an organic boron moisturizing soil, the silane coupling agent is preferably selected from any one or more of an amino silane coupling agent, an epoxy silane coupling agent, and a methacryloxy silane coupling agent, and the dispersant is preferably selected from any one or more of stearamide, oleamide, vinyl bisstearamide, and tristearic acid glyceryl.
[0036] In another typical embodiment of the present application, a HJT battery back metallization paste is provided. The HJT battery back metallization paste is prepared by mixing the aforementioned HJT battery back metallization paste composition.
[0037] The HJT battery back metallization slurry prepared by mixing the aforementioned HJT battery back metallization slurry composition is prepared by selecting the silver powder with a D90 particle size in the above range. On the one hand, it is beneficial to optimize the dense packing structure of the metal powder and develop a high-conductivity slurry that is particularly suitable for screen printing on the back of large-opening HJT batteries. On the other hand, it is beneficial to improve the compatibility of the organic carrier and the metal powder, improve the printability of the HJT battery back metallization slurry, and at the same time, reduce the viscosity and dosage of the HJT battery back metallization slurry, increase the line width of the back sub-grid line, and thus increase the short-circuit current. The combination of silver powder and silver-coated copper powder helps to improve the conductivity of the HJT battery back metallization slurry, thereby helping to balance the photoelectric conversion efficiency and low metallization cost of the HJT battery.
[0038] In one embodiment of the present application, the viscosity of the above-mentioned HJT battery back metallization paste is 50 to 800 Pa.s, and preferably the viscosity of the HJT battery back metallization paste at 10 revolutions is 200 to 550 Pa.s.
[0039] The viscosity of the metallization slurry on the back of the HJT battery has a great influence on its storage stability and printability: if the viscosity is too low at low speed, the silver powder moves significantly under the action of gravity, and the uniformity of the metallization slurry on the back of the HJT battery deteriorates with the extension of storage time. At the same time, if the viscosity of the metallization slurry on the back of the HJT battery is too large, although the stability can be improved, poor ink flow and poor ink spreading will occur during screen printing. At the same time, the high viscosity of the metallization slurry on the back of the HJT battery is not conducive to increasing the width of the secondary grid line. Therefore, when selecting the silver powder ratio, in addition to considering the effect of different silver powder combinations on electrical properties, the effect of viscosity on the use process of the slurry should also be considered. The above viscosity of the metallization slurry on the back of the HJT battery is preferred, so that the slurry has excellent rheological properties, which helps to improve the widening of the secondary grid line, meet the requirements of the small aspect ratio of the secondary grid line on the back of the HJT battery, and then increase the short-circuit current, which further helps to reduce the use of the metallization slurry on the back of the HJT battery.
[0040] In another typical embodiment of the present application, a HJT battery is provided, comprising a front metallization layer, an oxide conductive film TCO, a p-type amorphous silicon film pa-Si:H, an intrinsic amorphous silicon film ia-Si:H, a silicon wafer, an intrinsic amorphous silicon film ia-Si:H, an n-type amorphous silicon film na-Si:H, an oxide conductive film TCO, and a back metallization layer stacked in sequence, wherein the back metallization layer is formed by curing the above-mentioned HJT battery back metallization slurry.
[0041] This application aims at the characteristics of the back metallization of HJT batteries. By selecting silver powder with a D90 particle size in the above range, on the one hand, it is beneficial to optimize the dense packing structure of the metal powder and develop a high-conductivity slurry that is particularly suitable for screen printing on the back of large-opening HJT batteries. On the other hand, it is beneficial to improve the compatibility of organic carriers and metal powders, improve the printability of the metallization slurry on the back of HJT batteries, and at the same time, reduce the viscosity and dosage of the metallization slurry on the back of HJT batteries, increase the line width of the back sub-grid lines, and thus increase the short-circuit current. The combination of silver powder and silver-coated copper powder helps to improve the conductivity of the metallization slurry on the back of HJT batteries, thereby helping to balance the photoelectric conversion efficiency and low metallization cost of HJT batteries.
[0042] In one embodiment of the present application, the interval between adjacent secondary gate lines of the above-mentioned back metallization layer is 0.5-2.5 mm, and preferably the width of each secondary gate line is 35-75 μm, and preferably the aspect ratio of each secondary gate line is 2-4:10.
[0043] The wider the back sub-grid line of the HJT battery, the more helpful it is to increase the short-circuit current. On this basis, it is preferred that the aspect ratio of the back sub-grid line is within the above range, which is more conducive to reducing the amount of slurry used and ensuring a higher photoelectric conversion efficiency.
[0044] The beneficial effects of the present application are further illustrated below in combination with embodiments and comparative examples.
[0045] Examples 1 to 4
[0046] Silver powder is represented by 1#, 2#, 3# and 4# respectively, and the silver-coated copper powder is represented by 5#. The microscopic morphology of the five powders is as follows: Figure 1 As shown in Table 1, the five powders have different morphologies and particle sizes. The specific information is shown in Table 1.
[0047] Table 1
[0048]
[0049] In the preparation of silver paste, the mass ratio of metal powder, bisphenol A epoxy resin and dibutyl carbonate is fixed, and by changing the ratio of the three silver powders, 4 different low-temperature HJT battery back metallization pastes in Examples 1 to 4 (referred to as Paste1, Paste2, Paste3, Paste4, respectively) are obtained. The specific formula is shown in Table 2: The process flow of preparing silver-copper paste is: according to the formula, bisphenol A epoxy resin, dibutyl carbonate, and amide wax thixotropic agent (amide wax and lubricating ester are heated at 75°C to completely dissolve, and mixed with diethylene glycol butyl ether acetate in a mass ratio of 1:1 to obtain the amide wax thixotropic agent used in the present invention) are accurately weighed, added to a material tank, and silver powder and silver-coated copper powder are added under slow stirring. After the metal powder and the organic phase are fully infiltrated, the slurry is transferred to a three-roll mill for grinding. The gap parameters of the three rollers are 90 / 45, 30 / 15 and 20 / 10, and each gap is three-rolled twice.
[0050] Table 2
[0051]
[0052]
[0053] The viscosity curves of four HJT cell back metallization pastes are shown in Figure 2. Figure 3 As shown by Figure 3 It can be seen that with the increase of the content of small-particle spherical silver powder in the formula, the viscosity of the slurry gradually increases. Among them, Paste 4 with added nanopowder has the largest viscosity, and the viscosity at 10 revolutions is 525±12Pa.s. This is because the specific surface area of nano-spherical silver powder is large. When the organic components are the same, the organic content of silver powder coating per unit area is low, the lubrication effect is weakened, and the internal friction increases. The viscosity of the slurry has a great influence on its storage stability and printability: if the viscosity is too low at low revolutions, the silver powder moves significantly under the action of gravity, and the uniformity of the slurry deteriorates with the extension of storage time. At the same time, if the viscosity of the slurry is too high, although the stability can be improved, poor ink flow and poor ink spreading will occur during screen printing. At the same time, the high viscosity of the slurry is not conducive to increasing the width of the secondary grid line. Therefore, when selecting the silver powder ratio, in addition to considering the impact of different silver powder combinations on electrical properties, the impact of viscosity on the use of the slurry should also be considered.
[0054] Furthermore, in order to investigate the effects of different silver powder combinations on the electrical properties and photoelectric conversion efficiency of the back metallization paste of HJT cells, this study printed Paste 1, Paste 2, Paste 3, and Paste 4 on the back of the blue film by screen printing (using the same screen), and the same paste was used on the front. Cured at 200°C for 15 minutes to obtain different cells. Through IV testing and 3D morphology testing, the electrical properties, efficiency, and morphology data of different pastes were obtained, as shown in Table 3:
[0055] Table 3
[0056]
[0057] Compared with Paste 2, Paste 1 uses larger flaky silver powder. After the paste is cured, the flaky silver powder contacts in large quantities in a face-to-face and face-to-face manner, and its contact area is larger than that of spherical silver powder. At the same time, the larger flaky silver powder will reduce the resistance of the resin in the conductive path to electron transfer, so the volume resistivity (ρ) of Paste 1 is lower than that of Paste 2. On the other hand, the viscosity of Paste 1 is lower than that of Paste 2, so the secondary grid line is wider, which increases the short-circuit current (Isc) of the battery, while the smaller aspect ratio reduces the amount of metallization paste used on the back of the HJT battery. Therefore, it can be concluded that compared with small-particle flaky silver powder, large-particle flaky silver powder is more suitable for metallization paste on the back of HJT batteries.
[0058] When compounding silver powders of different morphologies and particle sizes, it is necessary to consider not only the conductive path formed by the flaky silver powder in the two-dimensional structure, but also the dense packing degree of the powder in the three-dimensional space. With the introduction of submicron spherical silver powder and nano spherical spherical powder (Paste 3 and Paste 4), the packing density of the system gradually increases. Some studies have shown that the particle size of large particles should be more than three times that of small particles in order to play a better filling role. The particle size of the large-particle flaky silver powder selected in this study is 10.7μm, which is more than 10 times that of the small-particle spherical silver powder, so it has a more obvious effect of reducing the volume resistivity. At the same time, the small-particle spherical silver powder can better fill the pyramid structure on the surface of the TCO film, so it can reduce the contact resistance. However, as the average particle size of the powder decreases, the viscosity of the slurry increases, which reduces the width of the secondary grid line and increases the aspect ratio. For the secondary grid line on the back of the HJT battery, a large width increases light reflection, thereby increasing the photon density and increasing the short-circuit current, and vice versa, it will reduce the short-circuit current. The experimental results also show that the short-circuit currents of Paste 1, Paste 3, and Paste 4 gradually decrease. Although Paste 4 has a lower volume resistivity, it cannot make up for the loss caused by the low current, so the efficiency is lower than Paste 3.
[0059] In summary, for the metallization paste used on the back of HJT cells, the larger-sized flaky silver powder should be selected with the smaller-sized spherical silver powder to significantly reduce the volume resistivity and contact resistance, but the effect of the paste viscosity on the short-circuit current should also be considered. The organic carrier developed by the present invention is prepared with a solvent that is highly compatible with the silver-coated copper powder, and the paste with the composite metal powder combination of flaky silver powder, spherical silver powder and silver-coated copper powder in a ratio of 46:16:31 has the highest photoelectric conversion efficiency.
[0060] Example 5
[0061] The difference from Example 3 is that the HJT battery back metallization paste includes 34.5 parts of silver powder 1#, 12 parts of silver powder 3#, 46.5 parts of silver-coated copper powder 5#, 3.7 parts of bisphenol A epoxy resin, 2.4 parts of diethylene glycol butyl ether acetate and 0.9 parts of amide wax lubricating thixotropic agent.
[0062] Example 6
[0063] The difference from Example 3 is that the HJT battery back metallization paste includes 23 parts of silver powder 1#, 8 parts of silver powder 3#, 62 parts of silver-coated copper powder 5#, 3.7 parts of bisphenol A epoxy resin, 2.4 parts of diethylene glycol butyl ether acetate and 0.9 parts of amide wax lubricating thixotropic agent.
[0064] Example 7
[0065] The difference from Example 3 is that the HJT battery back metallization paste includes 11.5 parts of silver powder 1#, 4 parts of silver powder 3#, 77.5 parts of silver-coated copper powder 5#, 3.7 parts of bisphenol A epoxy resin, 2.4 parts of diethylene glycol butyl ether acetate and 0.9 parts of amide wax lubricating thixotropic agent.
[0066] Example 8
[0067] The difference from Example 3 is that the HJT battery back metallization paste includes 59.4 parts of silver powder 1#, 2.6 parts of silver powder 3#, 31 parts of silver-coated copper powder 5#, 3.7 parts of bisphenol A type epoxy resin, 2.4 parts of diethylene glycol butyl ether acetate and 0.9 parts of amide wax lubricating thixotropic agent.
[0068] Example 9
[0069] The difference from Example 3 is that the organic carrier is hydrogenated bisphenol A epoxy resin.
[0070] Example 10
[0071] The difference from Example 3 is that the solvent is diethylene glycol butyl ether.
[0072] Embodiment 11
[0073] The difference from Example 3 is that the solvent is lauryl alcohol ester.
[0074] Example 12
[0075] The difference from Example 3 is that the solvent is terpineol.
[0076] Example 13
[0077] The difference from Example 3 is that the solvent is methyl adipate.
[0078] Embodiment 14
[0079] The difference from Example 3 is that the D90 particle size of the flaky silver powder is 6.5 μm.
[0080] Embodiment 15
[0081] The difference from Example 3 is that the D90 particle size of the spherical silver powder is 800 nm.
[0082] Example 16
[0083] The difference from Example 3 is that the D90 particle size of the spherical silver powder is 80 nm.
[0084] Embodiment 17
[0085] The difference from Example 3 is that the HJT battery back metallization paste includes 46 parts of silver powder 1#, 17 parts of silver powder 3#, 32 parts of silver-coated copper powder 5#, 1.7 parts of bisphenol A epoxy resin, 2.4 parts of diethylene glycol butyl ether acetate and 0.9 parts of amide wax lubricating thixotropic agent.
[0086] Embodiment 18
[0087] The difference from Example 3 is that the HJT battery back metallization paste includes 45 parts of silver powder 1#, 15 parts of silver powder 3#, 30 parts of silver-coated copper powder 5#, 5 parts of bisphenol A epoxy resin, 4.1 parts of diethylene glycol butyl ether acetate and 0.9 parts of amide wax lubricating thixotropic agent.
[0088] Embodiment 19
[0089] The difference from Example 3 is that the HJT battery back metallization paste includes 45 parts of silver powder 1#, 15 parts of silver powder 3#, 30 parts of silver-coated copper powder 5#, 4.1 parts of bisphenol A epoxy resin, 5 parts of diethylene glycol butyl ether acetate and 0.9 parts of amide wax lubricating thixotropic agent.
[0090] Comparative Example 1
[0091] The difference from Example 1 is that the metal powder in the metallization paste on the back side of the HJT battery is only silver powder.
[0092] Comparative Example 2
[0093] The difference from Example 1 is that the metal powder in the metallization slurry on the back side of the HJT battery is only silver-coated copper powder.
[0094] Comparative Example 3
[0095] The difference from Example 3 is that the proportion of silver powder in the HJT battery back metallization paste is 62wt.%, and the silver powder is silver powder 3#.
[0096] Comparative Example 4
[0097] The difference from Example 4 is that the proportion of silver powder in the HJT battery back metallization paste is 62wt.%, and the silver powder is silver powder 4#.
[0098] Comparative Example 5
[0099] The difference from Example 3 is that the HJT battery back metallization paste includes 45 parts of silver powder 1#, 14 parts of silver powder 3#, 30 parts of silver-coated copper powder 5#, 5.7 parts of bisphenol A epoxy resin, 4.4 parts of diethylene glycol butyl ether acetate and 0.9 parts of amide wax lubricating thixotropic agent.
[0100] Comparative Example 6
[0101] The difference from Example 3 is that the D90 particle size of the flaky silver powder is 15 μm.
[0102] The metallization paste of the back side of the HJT battery in Examples 5 to 19 and Comparative Examples 1 to 6 was printed on the back side of the blue film by screen printing, and the same paste was used on the front side. Cured at 200°C for 15 minutes to obtain different battery cells. The electrical properties, efficiency and morphology data of different pastes were obtained through IV testing and 3D morphology testing, as shown in Table 4. The viscosity of the metallization paste of the back side of the HJT battery in Examples 5 to 19 and Comparative Examples 1 to 6 at 10 revolutions is listed in Table 4.
[0103] Table 4
[0104]
[0105]
[0106] Process Example 1
[0107] The back metallization paste of the HJT cell of Example 3 was printed on the back of the blue film by screen printing, wherein the interval between the secondary grid lines of the back metallization layer was 0.5 mm, the opening of the screen was 30 μm, and the same paste was used on the front. Curing was performed at 200°C for 15 minutes to obtain different cells. The electrical performance, efficiency and morphology data of different pastes were obtained by IV testing and 3D morphology testing, as shown in Table 5.
[0108] Process Example 2
[0109] The back metallization paste of the HJT cell of Example 3 was printed on the back of the blue film by screen printing, wherein the interval between the secondary grid lines of the back metallization layer was 2 mm, the opening of the screen was 30 μm, and the same paste was used on the front. Curing was performed at 200°C for 15 minutes to obtain different cells. The electrical performance, efficiency and morphology data of different pastes were obtained by IV testing and 3D morphology testing, as shown in Table 5.
[0110] Table 5
[0111]
[0112] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0113] This application aims at the characteristics of the back metallization of HJT batteries. By selecting silver powder with a D90 particle size in the above range, on the one hand, it is beneficial to optimize the dense packing structure of the metal powder and develop a high-conductivity slurry that is particularly suitable for screen printing on the back of large-opening HJT batteries. On the other hand, it is beneficial to improve the compatibility of organic carriers and metal powders, improve the printability of the metallization slurry on the back of HJT batteries, and at the same time, reduce the viscosity and dosage of the metallization slurry on the back of HJT batteries, increase the line width of the back sub-grid lines, and thus increase the short-circuit current. The combination of silver powder and silver-coated copper powder helps to improve the conductivity of the metallization slurry on the back of HJT batteries, thereby helping to balance the photoelectric conversion efficiency and low metallization cost of HJT batteries.
[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A HJT battery back metallization paste composition, characterized in that: In parts by weight, the HJT battery back metallization paste composition comprises: 90-95 parts of metal powder; 0.5 to 10 parts of an organic carrier; and 0.5 to 5 parts of solvent; The metal powder includes silver powder and silver-coated copper powder, the silver powder includes a first silver powder and a second silver powder, the D90 particle size of the first silver powder is ≥ the D90 particle size of the second silver powder, and the D90 particle size of the first silver powder is 4 to 11 μm; The mass ratio of the silver powder to the silver-coated copper powder is 0.5 to 2:
1.
2. The HJT battery back metallization paste composition according to claim 1, characterized in that: The mass ratio of silver to copper in the silver-coated copper powder is 0.05-0.3:
1.
3. The HJT battery back metallization paste composition according to claim 1, characterized in that: The D90 particle size of the silver-coated copper powder is 5 to 8 μm.
4. The HJT battery back metallization paste composition according to claim 1, characterized in that: The first silver powder is flaky silver powder, and the second silver powder is spherical silver powder.
5. The HJT battery back metallization paste composition according to claim 4, characterized in that: The mass ratio of the flaky silver powder to the spherical silver powder is 23:1-8.
6. The HJT battery back metallization paste composition according to claim 5, characterized in that: The flaky silver powder has a layer thickness of 0.05 to 0.1 μm.
7. The HJT battery back metallization paste composition according to claim 5, characterized in that: The D90 particle size of the spherical silver powder is 300-800 nm.
8. The HJT battery back metallization paste composition according to any one of claims 4 to 7, characterized in that: The mass ratio of the flaky silver powder, the spherical silver powder and the silver-coated copper powder is 46:16:
31.
9. The HJT battery back metallization paste composition according to claim 1, characterized in that: The first silver powder and the second silver powder are both flaky silver powders; the D90 particle size of the flaky silver powder is 4 to 11 μm, and the thickness of the flaky silver powder is 0.05 to 0.1 μm.
10. The HJT battery back metallization paste composition according to claim 9, characterized in that: The mass ratio of the flaky silver powder to the silver-coated copper powder is 62:
31.
11. The HJT battery back metallization paste composition according to claim 1, characterized in that: The organic carrier is selected from any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, hexahydrophthalic acid bisglycidyl ester, and tetrahydrophthalic acid bisglycidyl ester.
12. The HJT battery back metallization paste composition according to claim 1, characterized in that: The solvent is selected from any one or more of dibutyl carbonate, N,N-dimethyldecylamine, diethylene glycol-2-ethylhexyl ether, diethylene glycol monohexyl ether, diethylene glycol butyl ether acetate, diethylene glycol butyl ether, dodecanol ester, terpineol, and methyl adipate.
13. The HJT battery back metallization paste composition according to claim 1, characterized in that: The HJT battery back metallization paste composition also includes 0.5 to 1.5 parts of an auxiliary agent.
14. The HJT battery back metallization paste composition according to claim 13, characterized in that: The auxiliary agent is selected from any one or more of a thixotropic agent, a silane coupling agent, and a dispersant.
15. A HJT battery back metallization paste, characterized in that: The HJT battery back metallization paste is prepared by mixing the HJT battery back metallization paste composition according to any one of claims 1 to 14.
16. The HJT battery back metallization paste according to claim 15, characterized in that: The viscosity of the HJT battery back metallization slurry is 50 to 800 Pa.s.
17. The HJT battery back metallization paste according to claim 16, characterized in that: The viscosity of the HJT battery back metallization slurry at 10 revolutions is 200-550 Pa.s.
18. A HJT cell, comprising a front metallization layer, an oxide conductive film TCO, a p-type amorphous silicon film pa-Si:H, an intrinsic amorphous silicon film ia-Si:H, a silicon wafer, an intrinsic amorphous silicon film ia-Si:H, an n-type amorphous silicon film na-Si:H, an oxide conductive film TCO, and a back metallization layer stacked in sequence, characterized in that: The back metallization layer is formed by curing the HJT battery back metallization paste according to any one of claims 15 to 17.
19. The HJT battery according to claim 18, characterized in that: The interval between adjacent auxiliary grid lines of the back metallization layer is 0.5-2.5 mm.
20. The HJT battery according to claim 19, characterized in that: The width of each of the auxiliary gate lines is 35-75 μm.
21. The HJT battery according to claim 19, characterized in that: The aspect ratio of each of the auxiliary gate lines is 2 to 4:10.
Citation Information
Patent Citations
Silver-coated copper powder, preparation method, application of silver-coated copper powder in silver-coated copper slurry and method for detecting compactness of silver coating layer in silver-coated copper powder
CN115805310A
Heat curable conductive paste composition
JP2013114837A
Conductive paste and electronic device
WO2022199083A1